Identifying transboundary ecotourism zones in surkhandarya region: Opportunities and prospects - Ravshanov Shokhrukh; Khursanov Dunyobek; Malikov Bobur; Eshmamatov Elshod; Abduvaliev Khayitboy (E3S Web of Conferences)
This article examines the issue of identifying transboundary ecotourism zones in the Surkhandarya region from both theoretical and practical perspectives. Within the framework of the study, the region’s natural-geographical conditions, ecosystems, and cultural heritage are comprehensively analyzed to assess the potential for ecotourism development. Additionally, the concept of transboundary ecotourism, its regional development strategies, and integrative aspects of cooperation with neighboring countries are explored. The criteria for delineating ecotourism zones, their compliance with tourism infrastructure, and principles of sustainable development are analyzed, leading to the development of scientifically grounded recommendations. The research findings contribute to the formulation of regional ecotourism policies and provide a scientific and practical basis for the effective utilization of ecotourism resources.